Access to public dental care facilities in Chandigarh - Himbala Verma; Arun K Aggarwal; Vidya Rattan; Utkal Mohanty (Wolters Kluwer Medknow Publications, 2012)
Objectives: The objective of the study was to determine the level of dental health care access and associated factors, at various public health facilities in the Union Territory (UT) of Chandigarh. Materials and Methods: A study was done using a multistage random sampling technique, to interview adult respondents at their homes and to interview the dentists in the public dental clinics and hospitals. Results: The mean composite access score was 59.2 (SD 18.9) in urban areas and 60.5 (SD 20.9) in rural areas (P=0.64) on a scale of 100. The mean score for the self-perceived condition of their oral health was 6.47 (95% CI 6.17 - 6.76). Thirty-four percent of the respondents did not contact a dentist despite having a problem in the last year, primarily because dental problems were not important for them (45%), they lacked time (22%), and took self-medication (16%). Overall 58% of the respondents suggested government clinics and 44% liked private dentists for treatment of dental cavities. The government setup was preferred because the facilities were cheaper and affordable. Conclusions: Dental health care access and only limited dental facilities were available in most of the dental clinics in Chandigarh. Self-reported dental problem was low, and people ignored their dental problems.